How Important Does Chemistry and Literacy? Bibliometric Analysis from 1993–2023 - Yuliana Dwi Asworo (Journal of Research in Environmental and Science Education, 2024)
Literacy is the ability to identify, understand, interpret, create, communicate and compute that involves a continuum of learning measured at different proficient levels. It become as important aspect in nation development since being functionally literate is fundamental to all forms of successes a student. Chemistry as a part of science education, also making the primary objective of education to be chemical literacy. The purpose of this study is to analyze the relationship between chemistry and literacy and see its trends to find the research opportunity for further research by conducting a comprehensive bibliometric analysis over the years. A total of 688 documents were collected using the VOSviewer software from 1973 indicating the beginning of the field until 2023, then analyzed 535 articles from the year 1993. There are 60 articles as the most published in the 2020 and the most cited papers from Timothy and Cynthia Shanahan in 2008 with 844 cited. Keyword such as “Students”, “Chemistry”, “Humans”, and “Scientific Literacy” was the trending topic in this research. Sri Rahayu from Indonesia was the most productive authors and Journal of Chemical Education was the most active source with 81 documents. Universitas Negeri Malang with 22 papers as the most productive institution, followed by Universitas Negeri Yogyakarta, Universitas Pendidikan Indonesia and Universitas Negeri Jakarta with 10 papers. The most prolific country with the most research is the United States, followed by Indonesia and United Kingdom. This review provides summary of the research as well as potential future prospects for the area.